HAK MASYARAKAT ADAT ATAS PENGELOLAAN TANAH ULAYAT YANG DISERTIFIKATKAN ATAS NAMA PEMERINTAH DESA - Anastasia Pricillia Wibowo (Fakultas Hukum Universitas Narotama, 2022)
The ulayat rights of indigenous peoples as a form or method of land ownership by legal institutions are widely available in the archipelago, and even constitute the largest number of land areas in Indonesia. The customary land of indigenous peoples is a form of customary community legal area whose ownership is controlled collectively by a group of tribes who inhabit a certain area led by a traditional shop or tuaka. In formal legality, the customary rights of indigenous peoples have a place in the national land law (UUPA), but at the law-in-action level they still lack legal protection when dealing with development interests, so that people who own customary rights often become marginalized. Which results in structural impoverishment Keywords: ulayat rights, village land, ulayat land and land law